The effect of sprint or endurance training on the aerobic:anaerobic capacities
A sprint training group (3,000 m/day with 30% at 100% VO2max or higher) and an endurance group (4,000 m/day with all at 80% VO2max intensity) were compared after six weeks of training. It was found that the anaerobic energy system was particularly adaptable to training and that the anaerobic and aerobic systems developed independently. The anaerobic energy system has the potential for greater levels of improvement than previously thought. Sprint training did not cause the existing level of endurance to deteriorate but with endurance training there was a slight, almost negligible, reduction in anaerobic capacity. This latter feature was caused by insufficient stimulation of the anaerobic energy system during the 80% intensity swimming. Endurance training improved the economy profile most and also made sprint training easier and more effective. Specific mode training will result in improvements in sprint characteristics. Implication: Training should include both categories of stimulation. It is incorrect to assume that one form of training will also alter the other. Coaches have to determine the workloads and programming items that will cause endurance adaptation at one time, and sprint adaptation at another. A table indicating factors that can be used to determine training content to meet this requirement is attached at the end of this Bulletin. (ICAR 1990-91 Report)